EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DAN NHT PADAPOKOK BAHASAN RELASI DAN FUNGSI DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS VIII SMP NEGERI DI KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Rahayu, Siti; Mardiyana, Mardiyana; Sari, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research aims at finding out: (1) which one results better mathematics learning achievement among type TAI, NHT, or conventional; (2) which one has better  mathematics learning achievement among students with AQ categories; (3) at each of  learning models, which students has better mathematics learning achievement with AQ categories; (4) at each of AQ categories, which one results better mathematics learning achievement among type learning models. This study was quasi-experimental research. The population of this study was all students in grade VIII SMP Pringsewu, Lampung. The sampling technique was done by stratified cluster random sampling. Data analysis tecnique was used to test the hypothesis was  two-ways analysis of variance with unbalanced cell as a 3x3 factorial design.The conclusions of the research were as follows. (1) Cooperative learning type TAI results better mathematics learning achievement than type NHT and conventional, and the achievement  of student mathematics learning by NHT is the same as the achievement conventional.  (2) The achievement  of student mathematics learning in climbers is the same as the achievement campers, students with climbers have better mathematics learning achievement than those with quitters, and the achievement  of student mathematics learning in campers is the same as the achievement quitters; (3)  in each learning models, the students mathematics learning achievment is in constancy with  result of AQ categories, (4) in each of AQ categories, students mathematics learning achievment is in constancy with result of learning models.Keywords: Team Assisted Individualization (TAI), Numbered Head Together (NHT), conventional,  Adversity Quotient (AQ)